TOURISM IN NATURAL AND AGRICULTURAL ECOSYSTEMS IN THE EIGHTEENTH AND NINETEENTH CENTURIES. - Fagnani, Martino Lorenzo, 1989- ([S.l.])
1 online resource.
Keywords: This book analyzes the roots of one of the main human activities that can be developed in natural and agricultural ecosystems: tourism. Attention to natural and agricultural ecosystems and their conservation has intensified in recent decades, responding to increasing social sensitivity to the environment, as also witnessed by Agenda 2030. The book explores the development of tourism in natural and agricultural ecosystems in the eighteenth and nineteenth centuries, when some of its essential features derived from the practices of exploration, scientific study, business, healing practices, and also a desire for personal growth. This research is intended to open up international scholarly debate and discussion and draw in contributions from all disciplines and geographical areas. In addition, it intends to add an important piece to the mosaic of international literature that has rarely considered the origins of nature and rural tourism in an array of practices not always embodying a stated intent of recreation. This book is based on handwritten documents and travelogues circulating during the period in question. Most of the travel experiences analyzed regard men and women of European descent, but their travels were global, with ecosystems considered on all populated continents. This volume is essential reading for students and scholars alike interested in tourism history and the history of science and travel.